2021
DOI: 10.1021/acscatal.0c05029
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Methanation on Cu-Cluster Decorated Zirconia Supports with Different Morphology: A Combined Experimental In Situ GIXANES/GISAXS, Ex Situ XPS and Theoretical DFT Study

Abstract: Subnanometer copper tetramer−zirconia catalysts turn out to be highly efficient for CO 2 hydrogenation and its conversion to methane. The cluster size and substrate morphology are controlled to optimize the catalytic performance. The two types of zirconia supports investigated are prepared by atomic layer deposition (∼3 nm thick film) and supersonic cluster beam deposition (nanostructured film, ∼100 nm thick). The substrate plays a crucial role in determining the activity of the catalyst as well as its cyclabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 70 publications
0
41
0
Order By: Relevance
“…The first challenge could be solved if spectra that correspond to unique structures could be isolated. To solve the first part, several approaches have been proposed, ranging from forward modelling 38,39 to spectral deconvolution methods, such as principal component analysis (PCA), 40 linear combination analysis, 41 and multivariate curve resolution-alternating least square (MCR-ALS). 40 The latter approaches are particularly attractive if a series of spectra are available, such as when the sample is exposed to reaction conditions, where the speciation of different structures of catalytically active metal complexes changes with the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The first challenge could be solved if spectra that correspond to unique structures could be isolated. To solve the first part, several approaches have been proposed, ranging from forward modelling 38,39 to spectral deconvolution methods, such as principal component analysis (PCA), 40 linear combination analysis, 41 and multivariate curve resolution-alternating least square (MCR-ALS). 40 The latter approaches are particularly attractive if a series of spectra are available, such as when the sample is exposed to reaction conditions, where the speciation of different structures of catalytically active metal complexes changes with the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…MCR-ALS. Because of the possible presence of mixed states of Cu electronic structure in the experimental XANES at all stages of the reaction, as evident from our previous work 40 on CO 2 methanation using CuO x clusters, the task of XANES data analysis is 2-fold: (1) speciation and (2) structural analysis of each species. Linear combination fit (LCF) and MCR-ALS are the most commonly used techniques for studying the composition of mixtures.…”
Section: Machine Learning Methodsmentioning
confidence: 99%
“…Because of the possible presence of mixed states of Cu electronic structure in the experimental XANES at all stages of the reaction, as evident from our previous work on CO 2 methanation using CuO x clusters, the task of XANES data analysis is 2-fold: (1) speciation and (2) structural analysis of each species. Linear combination fit (LCF) and MCR-ALS are the most commonly used techniques for studying the composition of mixtures. ,, LCF requires the use of known standards for the fitting, which is a limitation for nanomaterial studies because their XANES spectra change significantly between the bulk and nanomaterial for which there are often no standard spectra available.…”
Section: Machine Learning Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 summarizes the theoretical-study-only ALD articles found in the Web of Science and covered in this review. It is worth mentioning that this review mostly focuses on the theoretical-study-only ALD articles and does not cover the combined experimental and theoretical ones, which are cited here [ 75 , 76 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 ]. Figure 5 displays the publications, summarized in Table 2 , that are covered in this study.…”
Section: Theoretical Studies On Aldmentioning
confidence: 99%